Animal figure references in Contemporary Iraqi ceramics (Journal of the College of Basic Education, 2022)
The presence of the animal form as a direct word close to human existence has been represented in many of his works over time, as it is almost not devoid of art from those animal vocabulary whether it is part or all of it, and the potter has taken great care of this word and dealt with it through the ages and it has become evident in the ceramic achievements In contemporary Iraq, our study came (references of the animal form in contemporary Iraqi ceramics) in response to the research and knowledge of the types of these animals and how to deal with them and their causes.